2022
DOI: 10.3390/en15197101
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Optical and Thermal Performance of Direct Absorption Solar Collectors

Abstract: Solar energy is the most promising green energy resource, as there is an enormous supply of solar power. It is considered a good potential solution for energy crises in both domestic and industrial sectors. Nowadays, many types of solar systems are used for harvesting solar energy. Most of the research is focused on direct absorption solar collectors (DASCs) due to their ability to capture more solar energy. The effectiveness of DASCs is dependent on various factors, such as working fluid properties, geometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…The thermal efficacy of solar systems depends on the absorption properties of the base fluid. 8 Gholinia et al 9 conducted research on water, engine oil, and ethylene glycol by dispersing carbon nanoparticles. The results showed that engine oil exhibited superior temperature and flow characteristics compared to water.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal efficacy of solar systems depends on the absorption properties of the base fluid. 8 Gholinia et al 9 conducted research on water, engine oil, and ethylene glycol by dispersing carbon nanoparticles. The results showed that engine oil exhibited superior temperature and flow characteristics compared to water.…”
Section: Introductionmentioning
confidence: 99%
“…The direct volumetric conversion and storage of solar-thermal energy as sensible heat in the thermal storage fluids avoid the slow heat transfer from the outer surfaces to the inner storage media and homogenize the temperature distribution within the storage media [24]. Such design thus can avoid the potential overheating of the outer surface, and minimize the radiation and convection heat loss from the solar collector, which in turn enables achieving high energy conversion efficiency at medium-to-high temperatures [25]. Such nanofluid-based DASCs not only improve the sustainability of solar-thermal systems [26], but also can be coupled with photovoltaic and solar steam generation systems for multifunctional applications [27].…”
Section: Introductionmentioning
confidence: 99%